Identification of degradation risk areas and delineation of key ecological function areas in Qinling region - Xiaojuan Xu; Dayi Lin; Yue Yang; Jing Liu; Changxin Zou; Naifeng Lin; Fusheng Jiao; Qian Wu; Jie Qiu; Kun Zhang (Scientific Reports)
Abstract As a critical component of the geographical divide between the northern and southern regions of China, the ecological stability of the Qinling region has profound implications for ecological balance within China and across East Asia. However, the degradation risk areas of the Qinling region remain unclear, and there are gaps in the delineation of key ecological protection areas. This study examines the improvement and decline in the Qinling region from 2000 to 2023 in terms of ecosystem patterns, quality, and functions. Moreover, key ecological function and degradation risk zones were identified, and future development paths were proposed for the Qinling region. The findings indicate that: (1) Urban area expansion was the most rapid, increasing by about 1800 km², with an average yearly growth rate of 2.43%. Ecosystem quality increased in 48.07% of the Qinling region. The degradation risk zones of ecosystem quality and function were primarily located in the Sanjiangyuan, the Minshan-Qinghai-Tibet Plateau, and the Loess Plateau in Shaanxi, Henan, and Gansu. The core areas for water and soil conservation only accounted for 17.92% and 10.47%, respectively, mainly distributed across the Qinling-Daba Mountains. Based on ecological patterns, quality, functions, and ecological protection and restoration projects, the Qinling region has been divided into two majority categories and 16 subcategories: 7 ecologically key functional areas and 9 degradation risk areas. This study offers recommendations for formulating ecological protection and restoration policies, thereby promoting the sustainable development of the region’s ecology and economy.